The Development Model of Learning Shot Put Oriented by Playing for Elementary School Students (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
Research development of aim products in the form of a model of learning-oriented bullets starting play in an effort to create a situation of active learning. The research method used is the method of research development (research and development), of the Brog and Gall which is divided into two stages, namely the early research (needs analysis) and development. Research conducted at SDN Klojen in Malang city. The instruments used are the now and interviews. Data were analyzed with a qualitative analysis techniques and qualitative descriptive. Based on the results of the expert analysis of the game, Physical Education in Elementary School , Learning experts and experts of athletics (Shot Put) assessing learning models Shot Put berorintasi play is at 88.75% category with good qualifications and a small group of trial results and large group shows that the model of learning is playing berorintasi cartridges starting at 84.72% category with the qualification of â€œgoodâ€ so that learning the berorintasi bullet starting play have can be used as a model for improve the quality of learning making learning active and fun